Thymosin Alpha-1 Has no Beneficial Effect on Restoring CD4+ and CD8+ T Lymphocyte Counts in COVID-19 Patients - Wang, Zhenyan; Chen, Jun; Zhu, Cuiyun; Liu, Li; Qi, Tangkai; Shen, Yinzhong; Zhang, Yuyi; Xu, Lie; Li, Tao; Qian, Zhiping; Steinhart, Corklin R.; Lu, Hongzhou (Frontiers in Immunology, 2021)
Dysregulation of immune response was observed in COVID-19 patients. Thymosin alpha 1 (Tα1) is used in the management of COVID-19, because it is known to restore the homeostasis of the immune system during infections and cancers. We aim to observe the longitudinal changes in T lymphocyte subsets and to evaluate the efficacy of Tα1 for COVID-19. A retrospective study was conducted in 275 COVID-19 patients admitted to Shanghai public health clinical center. The clinical and laboratory characteristics between patients with different T lymphocyte phenotypes and those who were and were not treated with Tα1 were compared. Among the 275 patients, 137 (49.8%) were males, and the median age was 51 years [interquartile range (IQR): 37-64]. A total of 126 patients received Tα1 therapy and 149 patients did not. There were 158 (57.5%) patients with normal baseline CD4 counts (median:631/μL, IQR: 501 762) and 117 patients (42.5%) with decreased baseline CD4 counts (median:271/μL, IQR: 201 335). In those with decreased baseline CD4 counts, more patients were older (p<0.001), presented as critically ill (p=0.032) and had hypertension (p=0.008) compared with those with normal CD4 counts. There was no statistical difference in the duration of virus shedding in the upper respiratory tract between the two groups (p=0.214). In both the normal (14 vs 11, p=0.028) and the decreased baseline CD4 counts group (15 vs 11, p=0.008), duration of virus clearance in the patients with Tα1 therapy was significantly longer than that in those without Tα1 therapy. There was no significant difference in the increase of CD4+ (286 vs 326, p=0.851) and CD8+ T cell (154 vs 170, p=0.842) counts in the recovery period between the two groups with or without Tα1 therapy. Multivariate linear regression analysis showed that severity of illness (p<0.001) and Tα1 therapy (p=0.001) were associated with virus clearance. In conclusion, reduction of CD4+ T and CD8+ T cell counts were observed in COVID-19 patients. Tα1 may have no benefit on restoring CD4+ and CD8+ T cell counts or on the virus clearance. The use of Tα1 for COVID-19 need to be more fully investigated.